Organisational Learning: A Resource-Based View Analysis - Chukwuma, Isaac Onyeyirichukwu; Chukwuma, Patrick Chukwunwike; Madu, Ifeanyi Leo (International Journal of Scientific Research and Management (IJSRM), 2024)
This study theoretically analyzed the relationship between organisational learning (OL) and resource-based view (RBV) in line with examining the concept of OL, concept of RBV, nexus between OL and RBV, response between OL and RBV, calibrating the challenges in synergizing OL and RBV and exploring the competitive advantage in optimizing OL to feature non-substitutable, rare, inimitable, and valuable (NRIV) attributes of RBV. The methodology engaged was the narrative literature review which is validated by its potency to align numerous authors’ perspectives for correlation and explanation. The paper is of the position that OL and its components when optimally refined and optimized are capable of attaining NRIV status and can position an organization at the leading cadre in its industry. The review explored and uncovers relevant literature, and made postulations in comprehending and validating the dynamic relationship in the interplay between OL and RBV.